Associated SDOH needs of patients without health insurance and experiencing food insecurity - Suma K. Thareja; Spenser Marting; William Davies; Santhosi Samudrala; Ramsey Rayes; Marie Balfour; Ana Mia Corujo-Ramirez; Frances Carter; Benjamin Liu; Dylan Trinh; Thomas Ritter; Jessica Miller; et al. (Springer, 2024)
Abstract Although patients experiencing food insecurity commonly screen positive for a myriad of social determinants of health (SDOH) needs and chronic medical conditions influenced by diet, few studies have investigated associations within both uninsured and food insecure populations. We screened patients for food insecurity using the USDA six-item short form between October 2021 and April 2022. We then evaluated associations of food security status with nine separate SDOH needs and eight chronic medical conditions. In this cross-sectional study, of the 190 patients seen at a student-run free clinic serving patients without health insurance, 135 (71%) completed the SDOH survey. We identified chronic medical conditions via retrospective chart review and analyzed associations using multivariable logistic regressions adjusted for age and sex. Uninsured participants experiencing food insecurity (n = 22,16.3%) requested more support for: medications (adjusted odds ratio [AOR] = 7.28; 95% Confidence Interval [95% CI] = 2.33-23.2); p-value [P] =  < 0.001, housing (AOR = 9.99; 95% CI = 2.29-48.7; P = 0.002), utilities (AOR = 3.94; 95% CI = 1.07-13.5; P = 0.03), mental health resources (AOR = 4.54; 95% CI = 1.66-12.5; P = 0.003), health insurance (AOR = 2.86; 95% CI = 1.09-8.22; P = 0.04), and dental care (AOR = 3.65; 95% CI = 1.26-13.3; P = 0.03). These participants were more likely to have anxiety (AOR = 3.26; 95% CI = 1.23-8.38; P = 0.02) and depression (AOR = 2.88; 95% CI = 1.01-7.80; P = 0.04) diagnoses or symptoms. We also discovered that individuals aged 18-50 experiencing food insecurity had a higher number of health conditions (AOR = 6.3455; 95% CI = 1.49-26.99; P = 0.01), underscoring the profound impact of SDOH in younger populations. Understanding the interplay between food insecurity, SDOH needs, and medical conditions informs interventions, including food distribution programs and enhanced mental health resources.